Reception of Marriage Age Limit in Marriage Law in Indonesia - Bukido, Rosdalina; Haris, Chadijah; Rosyadi, Muhammad Arief Ridha; Suleman, Zulkarnain (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The determination of the age limit for marriage in the Marriage Law is controversial in Indonesian society. This paper aims to analyze the response of public acceptance of the new regulation on the age limit for marriage according to marriage law in Indonesia. The method used is a qualitative method with a grounded theory approach. The data were got through observation, interviews with informants, and documentation, which were analyzed through three stages: data reduction, data display, and conclusion. The results showed three forms of public acceptance of the new regulation on marriage’s age limit: dominant hegemony, negotiation, and oppositional reception. The diversity of public acceptance of the age limit for marriage according to the law is influenced by differences in the level of public education, community culture, and public understanding of the validity of the marriage. Developing a more intensive study by comparing various perspectives is necessary. Involvement of the public, government, and judicial institutions representing each region in Indonesia, including the islands of Java, Sulawesi, and Kalimantan, is very much needed in disseminating marriage law in Indonesia.